2019
DOI: 10.1523/jneurosci.3085-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Increased Lysosomal Exocytosis Induced by Lysosomal Ca2+ Channel Agonists Protects Human Dopaminergic Neurons from α-Synuclein Toxicity

Abstract: The accumulation of misfolded proteins is a common pathological feature of many neurodegenerative disorders, including synucleinopathies such as Parkinson's disease (PD), which is characterized by the presence of ␣-synuclein (␣-syn)-containing Lewy bodies. However, although recent studies have investigated ␣-syn accumulation and propagation in neurons, the molecular mechanisms underlying ␣-syn transmission have been largely unexplored. Here, we examined a monogenic form of synucleinopathy caused by loss-offunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(112 citation statements)
references
References 48 publications
5
107
0
Order By: Relevance
“…Based on these findings, induction of lysosomal exocytosis to promote cellular clearance has been proposed as an alternative therapeutic strategy to treat not only LSDs, but also other pathological conditions characterized by undigested substrates accumulation and overloaded dysfunctional lysosomes, such as several common neurodegenerative disorders [2,32]. For instance, promising results have been recently obtained by increasing lysosomal exocytosis with lysosomal Ca 2+ channel TRPML1 agonists in iPSC-derived dopaminergic neurons from PARK9 mutated Parkinson's disease patients [33]. Authors showed that lysosomal exocytosis is involved in clearing intracellular α-synuclein in human dopaminergic neurons and that mutations in PARK9 contribute to the α-synuclein storage.…”
Section: Lysosomal Exocytosismentioning
confidence: 99%
“…Based on these findings, induction of lysosomal exocytosis to promote cellular clearance has been proposed as an alternative therapeutic strategy to treat not only LSDs, but also other pathological conditions characterized by undigested substrates accumulation and overloaded dysfunctional lysosomes, such as several common neurodegenerative disorders [2,32]. For instance, promising results have been recently obtained by increasing lysosomal exocytosis with lysosomal Ca 2+ channel TRPML1 agonists in iPSC-derived dopaminergic neurons from PARK9 mutated Parkinson's disease patients [33]. Authors showed that lysosomal exocytosis is involved in clearing intracellular α-synuclein in human dopaminergic neurons and that mutations in PARK9 contribute to the α-synuclein storage.…”
Section: Lysosomal Exocytosismentioning
confidence: 99%
“…Loss of ATP13A2 function is also associated with α-syn accumulation [ 166 , 167 ]. IPSC-derived dopaminergic neurons from KRD exhibit decreased secretion of α-syn from the axon and the cell body, as well as a disruption of the lysosomal Ca 2+ homeostasis.…”
Section: Autophagosome/lysosome Regulationmentioning
confidence: 99%
“…IPSC-derived dopaminergic neurons from KRD exhibit decreased secretion of α-syn from the axon and the cell body, as well as a disruption of the lysosomal Ca 2+ homeostasis. Enhancing lysosomal exocytosis by overexpression of ATP13A2 helps to control the α-syn levels [ 166 , 167 ].…”
Section: Autophagosome/lysosome Regulationmentioning
confidence: 99%
“…Indeed, PARK9 regulates lysosomal exocytosis, a pathway that could be potentiated to reduce α-synuclein accumulation. Tsunemi demonstrated that TRPML1 agonists are able to increase lysosomal exocytosis, thus impairing α-synuclein intracellular levels (Tsunemi et al, 2019).…”
Section: Parkinson's Diseasementioning
confidence: 99%